A simulation approach for managing manufacturing processes and inbound logistics: a case study. (9th August 2007) - T.S. Chan, Felix; Chan, H.K.
This paper presents a case study of using simulation in managing cellular manufacturing process in a Small- and Medium-sized Enterprise (SME). A specific simulation approach, which can facilitate the SME to forecast how to manufacture a new product family in small batch size, was developed. Their competitive edges, which linking up with the dramatic changing market, can be improved without making investment prior to the actual production of the new products and without disturbing real operations. Material flow behaviour, utilisation of resources and manufacturing processes sequences are the criteria that decision makers are seeking for improvement through this study.